Pengembangan Profesionalisme Guru Melalui Pelatihan Komik Digital dengan Canva for Education - Hevy Risqi Maharani; Nila Ubaidah; Mochamad Abdul Basir; Dyana Wijayanti; Imam Kusmaryono; Mohamad Aminudin (Universitas Lancang Kuning, 2022)
The purpose of the service activity is to provide insight and improve the professionalism of teachers in Central Java in making interesting and interactive teaching materials for students, especially in making digital comics with the Canva for Education application. In general, the difficulties experienced by teachers in making digital comics are how to make comic designs easy and attractive. The Canva for Education application is one application that can be used to overcome these problems. Teachers can create digital comics using a wide selection of available templates. The implementation of this service is carried out online using Zoom Meeting and Google Classroom. The training was attended by approximately 100 participants from various regions in Central Java. The final result of the training activity is that teachers can create digital comics published on social media Instagram. It is intended that the results of digital comics that have been made by teachers can be useful for the general public, especially students who get related material.